2011
DOI: 10.1097/mca.0b013e3283478d40
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-1 and matrix metalloproteinase-12 gene polymorphisms and the outcome of coronary artery disease

Abstract: These findings showed a trend of the GG-A haplotype of MMP-1 G-1607GG/MMP-12 A1082G towards the prediction of future clinical events in patients with CAD and suggested a possible importance of these loci in the prediction of the prognosis of CAD. Studies with large sample size are warranted to better investigate this association, as MMP genotyping could aid in identifying patients who are likely to have unfavourable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Out of 59 qualified studies, 28 studies included Caucasians,8 10 18 20 24 27–29 32 35 37 39 41 43–45 49–51 55 56 21 studies included East Asians,11 17 21 22 25 26 31 33 34 38 42 47 48 53 54 57–59 eight studies included Middle Easterns,9 15 16 23 30 40 46 and two studies included mixed populations 19 36. There were 15 studies involving patients and controls matched on age 9 15 16 29 33 36 39 44 48 56 58.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 59 qualified studies, 28 studies included Caucasians,8 10 18 20 24 27–29 32 35 37 39 41 43–45 49–51 55 56 21 studies included East Asians,11 17 21 22 25 26 31 33 34 38 42 47 48 53 54 57–59 eight studies included Middle Easterns,9 15 16 23 30 40 46 and two studies included mixed populations 19 36. There were 15 studies involving patients and controls matched on age 9 15 16 29 33 36 39 44 48 56 58.…”
Section: Resultsmentioning
confidence: 99%
“…Although MMP-1 colocalizes with MMP-13 in the shoulder regions of inflamed human atheromatous plaques and that specific MMP-1 haplotypes associate with plaque burden, its direct role in atherosclerosis remains unclear. 7, 3133 Macrophage-specific transgenic mice expressing human MMP-1 had less advanced atherosclerosis, but overexpression of human tissue inhibitor of metalloproteinase-1 (TIMP-1, an inhibitor of collagenases and other MMPs) showed a tendency to reduce atherosclerotic lesions in apoE −/− mice. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Another study confirmed that MMP-7 was positively associated with carotid calcification 34. Furthermore, a study investigated haplotypes of MMP-1 and MMP-12 toward prediction of future clinical events in patients with coronary artery disease 38. This study found a trend for predicting events and prognosis, but it did not reach statistical significance due to low sample size.…”
Section: Mmp Polymorphisms and Susceptibility To Diseasementioning
confidence: 93%